2020
DOI: 10.14309/ctg.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

Rome III, Rome IV, and Potential Asia Symptom Criteria for Functional Dyspepsia Do Not Reliably Distinguish Functional From Organic Disease

Abstract: INTRODUCTION: Although the Rome criteria were created primarily for research purposes, it was an important question whether the Rome criteria can distinguish organic dyspepsia from functional dyspepsia (FD). We evaluated the accuracy of the Rome IV criteria in identifying patients with FD and compared the differences between the Rome IV, Rome III, and potential Asia criteria in identifying patients with FD. METHODS: In this cross-sectional study, we analyzed data from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…It not only affects the life and work of patients, but also brings economic pressure to patients and national medical services. According to the Rome IV diagnostic criteria, FD refers to the presence of the above symptoms, but no gastrointestinal organic or structural lesions explained by gastroenteroscopy, ultrasound, computed tomography, gastrointestinal barium meal examination and other examinations ( Wei et al, 2020 ). Clinically, FD can be divided into epigastric pain syndrome (EPS), postprandial distress syndrome (PDS), and EPS-PDS overlap group.…”
Section: Introductionmentioning
confidence: 99%
“…It not only affects the life and work of patients, but also brings economic pressure to patients and national medical services. According to the Rome IV diagnostic criteria, FD refers to the presence of the above symptoms, but no gastrointestinal organic or structural lesions explained by gastroenteroscopy, ultrasound, computed tomography, gastrointestinal barium meal examination and other examinations ( Wei et al, 2020 ). Clinically, FD can be divided into epigastric pain syndrome (EPS), postprandial distress syndrome (PDS), and EPS-PDS overlap group.…”
Section: Introductionmentioning
confidence: 99%
“…As the Rome criteria became more established over time for research, clinicians began to debate their use for clinical practice. [19][20][21][22][23] One example is related to the change in criteria for IBS from Rome III to Rome IV. The new criteria increased the specificity of the diagnosis at the expense of its sensitivity and identified a patient group with more severe disease, and the prevalence of IBS in the global study dropped by 50%.…”
Section: Challenges Relating To the Rome Symptom-based Criteria For C...mentioning
confidence: 99%
“…28 The discrepancy between the Rome research criteria and clinical diagnoses became even more prominent with the publication of the Rome IV criteria, where changes in specific parameters compared to Rome III made the diagnosis less prevalent and defined a population with more severe disease. [20][21][22][23][24]29 In addition, the extent to which doctors are familiar with and apply the Rome diagnostic criteria is not clear. This is particularly important because patients with DGBI are treated at multiple levels of care, including gastroenterologists, family physicians, internists, surgeons, and others.…”
Section: Challenges Relating To the Rome Symptom-based Criteria For C...mentioning
confidence: 99%
“…It has been reported that only about half of the patients visiting hospitals meet the Rome criteria [ 10 ] in a real-world clinical setting. Recent reports in Asia also indicate that the Rome criteria for FD is suitable only in certain cases [ 11 , 12 , 13 , 14 , 15 , 16 ], meaning there are many dyspeptic patients who do not meet the Rome criteria, which we call non-FD patients in this study.…”
Section: Introductionmentioning
confidence: 97%